Desain Eksperimen pada DIVo 3.0 - Fonda, Debora; Anne Y A, Debora (Jurnal Titra, 2013)
DIVo is one of media that share information for students in Petra Christian University. The current version of DIVo use television as media for sharing information, and later, DIVo 3.0 will use mobile unit and wall mount. DIVo 3.0 will be distributed in 39 place, 31 of those are mobile unit. This study was conducted to determine the suitable layout design for DIVo so the information provided in the mobile unit DIVo can be clearly understood by students.Literature study and experiments were done to determine the details that should be used for Divo 3.0. Design of experiments was used to determine factors which are affecting the clarity of information. Factorial design is used as experiment design method and location for experiment is in 2 area in P building that categorized in different luminance. The experiment results showed that zoning, time of display, and colour combination of running ticker affects the clarity of information significantly. The best combination that gives the best clarity of information is using 1 main content area and 1 running ticker area, displayed for 10 seconds. White font in black background running ticker with speed rate 60 words per minute make the running ticker can be read clearly.